Ethics desk reference for counselors - Barnett, Jeffrey E.; Johnson, W. Brad (American Counseling Association, 2015)
The second edition of this highly practical and easily understood handbook provides counselors and students with the means to quickly apply the 2014 ACA Code of Ethics to practice and to professional roles and activities. It contains on-point recommendations for each standard of the Code, a decision-making model, and a listing of ethics resources. Part I presents each section of the Code, along with a brief commentary that emphasizes its most essential elements, common ethical dilemmas and problems relevant to that section, and specific strategies for risk prevention and positive practice. P.